2014
DOI: 10.1002/chem.201403518
|View full text |Cite
|
Sign up to set email alerts
|

2‐Chloro‐Azaborolyl Anion: A Source of 1,2‐Azaborole Isosteric to Cyclopentadienylidene

Abstract: Azaborolyl anions, the five-membered BN heterocycles, have attracted a considerable attention due to their aromaticity and isoelectronic relationship with ubiquitous cyclopentadienyl ligands. Besides their syntheses and applications in the preparation of metal complexes, the other aspects of their chemistry have been virtually unexplored. Reduction of the azabutadienyl chelate boron dichloride [ArNC(R)CHC(R)]BCl2 (2, Ar=2,6-Me2 C6 H3 , R=tBu) with two equivalents of potassium yielded the novel 2-chloro-azabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…The product was identified as iminoborane 2 by 1 H, 13 C, and 11 B NMR spectroscopy, EI mass spectrometry, and elemental analysis. The 1 H and 13 C NMR spectra show peaks at δ = 6.47 and 189.6 ppm for the C=CH proton and the C=N carbon atom in the BC 3 N five‐membered ring, respectively, similar to those reported for the donor‐stabilized iminoborane . However, the 11 B NMR spectrum of 2 exhibits a resonance at δ = 10.3 ppm, which is significantly shifted upfield, relative to the value of δ = 23.5 ppm reported for the iminoborane, probably due to the conjugation between the B=N and N=C bonds.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The product was identified as iminoborane 2 by 1 H, 13 C, and 11 B NMR spectroscopy, EI mass spectrometry, and elemental analysis. The 1 H and 13 C NMR spectra show peaks at δ = 6.47 and 189.6 ppm for the C=CH proton and the C=N carbon atom in the BC 3 N five‐membered ring, respectively, similar to those reported for the donor‐stabilized iminoborane . However, the 11 B NMR spectrum of 2 exhibits a resonance at δ = 10.3 ppm, which is significantly shifted upfield, relative to the value of δ = 23.5 ppm reported for the iminoborane, probably due to the conjugation between the B=N and N=C bonds.…”
Section: Resultssupporting
confidence: 64%
“…In previous studies, we found that the reaction of 1 with the organic azide ArN 3 offered the intramolecular donor‐stabilized iminoborane by elimination of KCl . This result prompted us to investigate its reaction with diazomethanes, with the expectation of synthesizing the corresponding methyleneboranes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently reportedt he synthesis and borylene-like reactivity of the 2-chloro-azaborolyl anion (LBCl) À K + (THF) (1, L = [ArNC(R)CHC(R)] À ;A r = 2,6-Me 2 C 6 H 3 ,R = tBu, Scheme 2). [12] This promptedu st oexaminet he reactions of 1 with elemental chalcogens for the furtheru nderstanding of the chemical [ properties of this unique masked heterocylic borylene. Herein, we report the reaction of 1 with elemental sulfur,l eading to the isolation of the first boron persulfide LB(h 2 -S 2 )( 2).…”
mentioning
confidence: 99%